Estrogenic and anti‐estrogenic activity of butylparaben, butylated hydroxyanisole, butylated hydroxytoluene and propyl gallate and their binary mixtures on two estrogen responsive cell lines (T47D‐Kbluc, MCF‐7). Issue 7 (19th February 2018) - Pop, Anca; Drugan, Tudor; Gutleb, Arno C.; Lupu, Diana; Cherfan, Julien; Loghin, Felicia; Kiss, Béla
Abstract: The estrogenic and anti‐estrogenic effects of butylparaben (BuPB), butylated hydroxyanisole (BHA), butylated hydroxytoluene (BHT) and propyl gallate (PG) were evaluated for individual compounds as well as for binary mixtures, using an estrogen‐dependent reporter gene assay in T47D‐Kbluc breast cancer cells and an estrogen‐dependent proliferation assay in MCF‐7 breast cancer cells. In terms of estrogenicity the potency of the selected compounds increased from BHA < PG < BuPB in the luciferase assay (with BHT showing no significant estrogenic activity), while in the proliferation assay the following order was observed: BHT < BHA < BuPB (with PG showing no significant estrogenic activity). Non‐monotonic dose–response curves were obtained for BuPB (in both assays) and PG (in the luciferase assay), respectively. In the presence of estradiol, a significant anti‐estrogenic activity was observed in both cell lines for PG, BuPB and BHA, while BHT showed weak anti‐estrogenic activity only in T47D‐Kbluc cells. The evaluation of binary mixtures confirmed the endocrine disruptive potential of the compounds, their individual potency being correlated with that of the mixtures. All mixtures were able to reduce the estradiol‐induced luminescence or cell proliferation, an effect that was accurately predicted by the dose addition mathematical model, suggesting the same (or at least partially overlapping) modes of action for the tested compounds. The results of the present study emphasize the importance of a cumulative risk assessment of endocrine disruptors. Abstract : The estrogenic and anti‐estrogenic effects of butylparaben, butylated hydroxyanisole, butylated hydroxytoluene and propyl gallate were evaluated for individual compounds and selected binary mixtures, using two in vitro assays. All compounds displayed estrogenic and/or anti‐estrogenic activity in at least one of the assays and there was a good correlation between the individual potencies of compounds and that of binary mixtures. The anti‐estrogenic effect of mixtures was predicted by the dose addition model. These results emphasize the importance of a cumulative risk assessment of endocrine disruptors.